STRATEGIES OF PONDOK PESANTREN IN NURTURING AND INCREASING COMMUNITY INTEREST IN RELIGIOUS ACTIVITIES - Irfan Rizkiana Raja Nugraha; Djuwairiyah Djuwairiyah; Agus Fakhruddin; Cucu Surahman (Fakultas Tarbiyah, Universitas Ibrahimy, 2025)
In the context of Islamic Religious Education in Indonesia, Islamic boarding schools (pesantren) play an important role in fostering the moral and spiritual development of society. However, the reality shows that many Islamic boarding schools face challenges in attracting community participation. This study aims to analyze the strategies implemented by the Al-Futuhat Islamic Boarding School in Garut to increase community interest in religious activities. This study uses a qualitative approach. The results of the study show that the Al-Futuhat Islamic Boarding School carries out 3 strategies to attract community attention and participation, namely: (1) learning innovation by promoting the 'talaran nadhom' method, (2) innovative programs for the community such as free hajj-umrah and others, (3) establishing close cooperation with community leaders and graduates of this Islamic boarding school.